Histology of neovascular myopic macular degeneration - Jonas, Shefali B.; Panda-Jonas, Songhomitra; Jonas, Jost B.; Jonas, Rahul A. (Scientific reports, 2021)
To assess the histological correlate of neovascular or exudative myopic macular degeneration (nMMD) in highly myopic human eyes, we examined histomorphometrically histologic sections of enucleated eyes of Caucasian patients. The study included 284 eyes (age: 61.9 ± 13.7 years; range: 24-89 years; axial length: 25.5 ± 3.1 mm; range: 20-37 mm). An nMMD was detected in 5 eyes (axial length: 29.6 ± 2.6 mm; range: 26.0-31.0 mm). All these eyes showed within or close to the nMMD a macular Bruch’s membrane (BM) defect, fibrous tissue with erythrocyte-filled blood vessels, and proliferations of irregularly pigmented and irregularly piled-up retinal pigment epithelium (RPE) cells each of which was connected with a curled-up, PAS (Periodic-Acid-Shiff)-positive membrane. The nMMD lesions were covered by proliferated RPE cells. RPE cells were not detected within the retina. In binary regression analysis, a higher nMMD prevalence was associated with a higher prevalence of macular BM defects (odds ratio: > 1000; P < 0.001), while the association with axial length was not significant (P = 0.43) in that model. After adjustment for the presence of macular BM defects, the nMMD prevalence was not associated with BM thickness (measured at the posterior pole, equator-posterior pole midpoint, equator and shortly posterior to the ora serrata) (P = 0.10; P = 0.87; P = 0.40; and P = 0.36, respectively), RPE cell layer thickness (P = 0.83; P = 0.79; P = 0.31; P = 0.38, resp.), RPE cell density (P = 0.56; P = 0.91; P = 0.47; P = 0.87, resp.), choriocapillaris thickness (P = 0.47; P = 0.93; P = 0.41; P = 0.75, resp.), and choriocapillaris density (P = 0.99; P = 0.94; P = 0.17; P = 0.97, resp.). The results suggest that nMMD is characterized by a fibrous pseudo-metaplasia of the RPE and is strongly associated with macular BM defects, without other detected histomorphometric differences in thickness or density of the RPE, BM, and choriocapillaris.
Gesehen am 17.08.2023